Electrochemical Generation of Complexes Containing Heterometallic Trinuclear Triangular Metal-Sulphur-Cubiodal M’M2S24+ Core (where M and M’ = Mo and W): Synthesis and Study of Physico-chemical Behaviour - Sah2, Ramjee; Kumar3, Ashwini (Asian Journal of Chemistry, 2013)
Chromatographic separation of mixture leads to the isolation of molybdenum-tungsten mixed-metal clusters [MoW2S4(H2O)9]4+ and [WMo2S4(H2O)9]4+. From the aqua ion the corresponding oxalato-derivatives as [MoW2S4(C2O4)3(H2O)3]2- and [WMo2S4(C2O4)3(H2O)3]2- are isolated. The peak positions of the two big bands in each infrared spectrum of the four aqua clusters, [Mo3S4(H2O)9]4+, [W3S4(H2O)9]4+, [MoW2S4(H2O)9]4+ and [WMo2S4(H2O)9]4+ in the 550-400 cm-1 region shift to lower wave number when the molybdenum atom is replaced by tungsten. The cyclic voltammogramms of Cs2[MoW2S4(C2O4)3(H2O)3] (1)B and Cs2[WMo2S4(C2O4)3(H2O)3] (2) shows three consecutive one-electron reduction steps in the aqueous medium with supporting electrolyte, KCl at -0.84, -1.40, -1.78 and -0.73, -1.22, -1.66 V, respectively. These steps correspond to the change of oxidation states of three metals in each cluster with the following electronic configuration M36 ® M37 ® M38 ® M39. The half wave potential E1/2 are significantly dependent on the cluster metals. In all the reduction processes the [MonW3-nS4(C2O4)3(H2O)3]2- clusters (n = 0-3) are easily reduced with the increase in the number of Mo(n) in the clusters. The proceeding reduction centre of themolybdenum-tungsten mixed metal clusters is mainly on the Mo atom(s) rather than Watoms.